Pemanfaatan Serat Sabut Kelapa dan Serat Bendrat untuk Dinding Beton Ringan Pracetak Tulangan Anyaman Bambu dengan Agregat Limbah Batu Apung - Suparjo, Suparjo (Department of Civil Engineering, Diponegoro University, 2005)
Based on assumption thatÂ bamboo have a high tensile strength, most research about bamboo application as reinforced concrete has been done in the National and International level. This research tries to use bamboo as reinforced concrete for the light concrete by adding coconut fiber, and bendrat fibre. It is expected to increase the compressive strength, the tensile strength of concrete, and bending strength of precast wall-plate. The result showed it that the optimum compressive strength is in the mixture compositio. The compositon of coconut fiber reach optimum at 0,50 % , and bendrat fibre optimum at 1,00 % of mixture volume. Pre-cast wall plate with bamboo galah non fiber as bar by size 3 mm x 15 mm and plate specimen is made by thickness 30 mm, 40 mm, and 50 mm, enable to carry loadÂ 103 kg, 128 kg, and 159 kg respectively. By adding coconut fibre 0,50 % will increase the bending strength as follow , 13,31 %, 11,45 %, and 13,04 % respectively. On the other words, by adding bendrat fibre 1,00 % will increase the bending strength as follow , 13,96 %, 20,40 %, and 18,92 % respectively. Base on those resuts can be conclude that precast of plate light concrete by adding coconut fiber with tickness 3 cm is strong enough to carry live load (100 kg).Keywords: bamboo reinforced, coconut fiber, bendrat fibre, compressive strength, tensile strength, and bending strengthPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3924[How to cite: Suparjo, 2005, Pemanfaatan Serat Sabut Kelapa dan Serat Bendrat untuk Dinding Beton Ringan Pracetak Tulangan Anyaman Bambu dengan Agregat Limbah Batu Apung, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 3, pp. 86-95]Â